Cost Analysis for IoT Based Condition Based Maintenance to Increase Productivity - Dewanti, Dewanti; Singgih, Moses Laksono (IPTEK Journal of Proceedings Series, 2019)
Condition Based Maintenance (CBM) is one of maintenance method that believed to be the most effective at reduction of cost and number of activities than the other maintenance methods. Degradation monitoring condition is an important things in order to get effective CBM system. The rapid development in information and communication has lead our industrial phase to industry 4.0, where are lot of smart objects can be connected and integrated in one network system, which is called Internet of Things (IoT). IoT facilitates monitoring and controlling to an object, and help maintenance system to monitor, record, and analyze the degradation of the object. Furthermore, with real time monitoring, system could detect and make decision when is maintenance activity should be done with consideration in cost. This research focused in the issue of integration of many smart objects to support CBM activities in cost reduction and IoT decision making with cost minimization as criteria. Cost analysis has been done using Activity Based Costing (ABC) and mathematical model has been constructed for decision making criteria which will be tested with numerical test using the data that gathered from company which applied IoT system. There are three condition which are tested: system without IoT implementation, current system with IoT implementation (auto shutdown when machine stroke reaches 300), and IoT system that consider the degradation condition to shut down. The result shows that IoT based CBM system that consider degradation level will incur optimal number of activities which resulting in fewer cost that the other systems. With fewer activity maintenance than auto-shutdown at 300 strokes, shows that the productivity increase without any delay due to maintenance